Moxifloxacin Pharmacokinetics, Cardiac Safety, and Dosing for the Treatment of Rifampicin-Resistant Tuberculosis in Children. (21st July 2021) - Radtke, Kendra K; Hesseling, Anneke C; Winckler, J L; Draper, Heather R; Solans, Belen P; Thee, Stephanie; Wiesner, Lubbe; van der Laan, Louvina E; Fourie, Barend; Nielsen, James; Schaaf, H Simon; Savic, Radojka M; et al.
Abstract: Background: Moxifloxacin is a recommended drug for rifampin-resistant tuberculosis (RR-TB) treatment, but there is limited pediatric pharmacokinetic and safety data, especially in young children. We characterize moxifloxacin population pharmacokinetics and QT interval prolongation and evaluate optimal dosing in children with RR-TB. Methods: Pharmacokinetic data were pooled from 2 observational studies in South African children with RR-TB routinely treated with oral moxifloxacin once daily. The population pharmacokinetics and Fridericia-corrected QT (QTcF)-interval prolongation were characterized in NONMEM. Pharmacokinetic simulations were performed to predict expected exposure and optimal weight-banded dosing. Results: Eighty-five children contributed pharmacokinetic data (median [range] age of 4.6 [0.8–15] years); 16 (19%) were aged <2 years, and 8 (9%) were living with human immunodeficiency virus (HIV). The median (range) moxifloxacin dose on pharmacokinetic sampling days was 11 mg/kg (6.1 to 17). Apparent clearance was 6.95 L/h for a typical 16-kg child. Stunting and HIV increased apparent clearance. Crushed or suspended tablets had faster absorption. The median (range) maximum change in QTcF after moxifloxacin administration was 16.3 (–27.7 to 61.3) ms. No child had QTcF ≥500 ms. The concentration–QTcF relationship was nonlinear, with a maximum drug effect (Emax ) of 8.80 ms (interindividual variability = 9.75 ms). Clofazimine use increased Emax by 3.3-fold. Model-based simulations of moxifloxacin pharmacokinetics predicted that current dosing recommendations are too low in children. Conclusions: Moxifloxacin doses above 10–15 mg/kg are likely required in young children to match adult exposures but require further safety assessment, especially when coadministered with other QT-prolonging agents. Abstract : Weight, human immunodeficiency virus status, stunting, and formulation influence moxifloxacin pharmacokinetics in children. Moxifloxacin prolongs the QT interval, but no severe prolongation events occurred. The effect was increased with clofazimine cotreatment. Higher moxifloxacin doses are needed to match adult exposures.